Proof of Concept: Matrix metalloproteinase inhibitor decreases inflammation and improves muscle insulin sensitivity in people with type 2 diabetes - Frankwich Karen; Tibble Courtney; Torres-Gonzalez Moises; Bonner Mariah; Lefkowitz Roy; Tyndall Matt; Schmid-Schönbein Geert W; Villarreal Francisco; Heller Mike; Herbst Karen (BMC, 2012)
Abstract Background Obesity is a state of subclinical inflammation resulting in loss of function of insulin receptors and decreased insulin sensitivity. Inhibition of the inflammatory enzymes, matrix metalloproteinases (MMPs), for 6 months in rodent models restores insulin receptor function and insulin sensitivity. Methods This 12-week double-blind, randomized, placebo (PL)-controlled proof-of-concept study was performed to determine if the MMP inhibitor (MMPI), doxycycline, decreased global markers of inflammation and enhanced muscle insulin sensitivity in obese people with type 2 diabetes (DM2). The study included non-DM2 controls (n = 15), and DM2 subjects randomized to PL (n = 13) or doxycycline 100 mg twice daily (MMPI; n = 11). All participants were evaluated on Day 1; MMPI and PL groups were also evaluated after 84 days of treatment. Results There was a significant decrease in inflammatory markers C-reactive protein (P < 0.05) and myeloperoxidase (P = 0.01) in the MMPI but not PL group. The MMPI also significantly increased skeletal muscle activated/total insulin signaling mediators: 3'phosphoinositide kinase-1 (PDK1) (p < 0.03), protein kinase B (PKB/Akt) (p < 0.004), and glycogen synthase kinase 3ß (GSK3ß) (p < 0.03). Conclusions This study demonstrated short term treatment of people with diabetes with an MMPI resulted in decreased inflammation and improved insulin sensitivity. Larger, longer studies are warranted to determine if doxycycline can improve glucose control in people with diabetes. Trial Registration Clinicaltrials.gov NCT01375491